The Effect of Pravastatin on Hypoxia Inducible Factor-1-Alpha (HIF-1-A) Expression on the Placenta of Preeclampsia Wistar Rats - Predixon Leonardo Napitupulu; Herman Kristanto; Putri Sekar Wiyati; Yuli Trisetyono; Besari Adi Pramono (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Background: Preeclampsia (PE) is hypertension in pregnancy that currently occurs starting from the time of placentation and is 1 of the five leading causes of maternal death. The main cause of preeclampsia is the placenta, which is hypoxic, and the spiral artery remodeling fails. Hypoxia-inducible factor-1-alpha (HIF-1-A), a marker in the nucleus, is overexpressed during tissue hypoxia. Pravastatin has a pleiotropic effect as the synthesis of nitric oxide (NO), a strong vasodilator to correct hypoxia. This study aims to explore the potential of pravastatin against functional abnormalities or placental hypoxia through in vivo HIF-1-A expression. Methods: This study is an experimental study using female Wistar rats (Rattus norvegicus) induced by preeclampsia. Assessment of HIF-1-A expression was carried out by immunohistochemistry. Data analysis was performed using SPSS, and then univariate and bivariate tests were performed. Results: Administration of pravastatin at a dose of 10 mg/kg BW showed the most optimal potential in reducing the expression of HIF-1-A protein, indicating tissue hypoxia. Pravastatin doses of 2.5 mg/kg BW and 5 mg/kg BW also could reduce HIF-1-A protein expression better than the K+ group who were not given pravastatin. Conclusion: Pravastatin can reduce the expression of HIF-1-A protein in pre-eclamptic rats, which indicates the potential of pravastatin to reduce the incidence of preeclampsia.